Analisis dan Audit Sistem Manajemen Keamanan Informasi (SMKI) pada Instansi Perpustakaan dan Arsip Daerah Kota Salatiga - Gregorius Anung Hanindito (Jurnal Nasional Teknologi dan Sistem Informasi, 2017)
Rapidly changing in Information Technology initiates various innovation that aims to provide convenience for enterprises, organizations, and institutions. Innovation is created to ease users in completing tasks and activities. Unfortunately, easiness in innovation gives chances of fraud and disruption to happen. This paper discusses how countermeasures on those issues are done in Salatiga Library and Archive Office using 4 (four) control aspects in Information System Audit: environtment security control, physical security control, logical security control, and IS operation control. This paper use three step of method, they are: planning and preparation, implementation, and reporting. The aim of this research is to examine the Information System security level in Salatiga Library and Archive Office.